PENGARUH KONSERVATISME AKUNTANSI, KOMISARIS INDEPENDEN DAN INCOME SMOOTHING TERHADAP KUALITAS LABA (Pada Perusahaan Manufaktur Sektor Industri Barang Konsumsi yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2021) - Nurjannah Nurjannah; Yunina Yunina; Nur Afni Yunita; Muammar Khaddafi (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Malikussaleh, 2024)
AbstractThis study aims to examine the effect of accounting conservatism, independent commissioners and income smoothing on earnings quality. The dependent variable in this study is earnings quality and the independent variables in this study are accounting conservatism, independent commissioners and income smoothing. The population in this study are manufacturing companies in the consumer goods industry sector which are listed on the Indonesian Stock Exchange (IDX) for 2019-2021 with a total of 54 companies. Sampling in this study used purposive sampling, namely sampling based on certain criteria and obtained as many as 42 companies with 126 observational data. This research is a quantitative research with secondary data sources including the company's annual financial reports obtained through the website www.idx.co.id and the official website of each company. There are several research methods used to achieve the objectives of this study including descriptive statistical analysis, model selection test, classic assumption test. Data collection techniques in this study are the method of documentation and literature study. Data analysis in this study used panel data regression using EViews 10 software. The results showed that accounting conservatism had a negative effect on earnings quality, independent commissioners had a positive effect on earnings quality and income smoothing had no effect on earnings quality. Keywords: accounting conservatism, independent commissioners, income smoothing and earnings quality.